ISOLASI DAN IDENTIFIKASI KAPANG ENDOFIT ASAL AKAR TANAMAN KUNYIT (Curcuma longa) SEBAGAI ANTIMALARIA - Eris Septiana; Fauzy Rachman; Sylvia J.R. Lekatompessy; Harmastini I. Sukiman; Partomuan Simanjuntak (BERITA BIOLOGI, 2018)
Malaria is still the leading cause of death worldwide with nearly half the world's population at risk. Parasitic resistance to existing antimalarial drugs in the market makes the search for a source of new drugs from nature is very important. Therefore, the aims of this study are to determine in vitro antimalarial activity of endophytic fungi extract from turmeric root and to identify the selected isolate molecularly. Heme polymerization inhibition method was used as in vitro antimalarial assay. The selected isolate was thrn identified using ITS1, ITS2, and 5.8S sequences of rDNA. The result of this study obtained 16 isolates of endophytic fungi from root of turmeric plant with isolate code were of K.Cl.Sb.A1 - K.Cl.Sb.A16. All of the ethyl acetate extracts of isolated endophytic fungi have heme polymerization inhibition activity. K.Cl.Sb.A11 was the most active isolate on heme polymerization inhibition test with 94,31% at concentration of test material at 8 mg/mL and IC50 value at 1.84 mg/mL. Molecular analysis showed that K.Cl.Sb.A11 isolate was Penicillium sp. and potentially developed as an antimalarial drug.